1989
DOI: 10.1002/jbmr.5650040317
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of inositol phosphate formation in ros 17/2.8 cell membranes by guanine nucleotide, calcium, and parathyroid hormone

Abstract: In addition to stimulation of cyclic AMP, parathyroid hormone (PTH) may influence cellular events by utilizing other pathways of hormone action, such as the generation of inositol phosphates (IPs). We sought to examine this potential action of PTH by assessing the formation of inositol phosphates in PTH-sensitive ROS 17/2.8 cells. The polyphosphoinositides were labeled by growing the cells with [3H]inositol following which cell homogenates were prepared. The nonhydrolyzable guanine nucleotide, GTP gamma S, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(4 citation statements)
references
References 39 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…TRPC channel activation is downstream of phospholipase C (PLC), so G protein-coupled receptor signaling events that activate PLC are poised to open VGCCs. Of note, the parathyroid hormone that stimulates Ca 2+ influx through VGCCs in ROS 17/2.8 activates PLC (90), and ROS 17/2.8 cells have TPRC3 transcripts (91).…”
Section: Potential Mechanisms Of Voltage-gated Ca 2+ Channel Regulati...mentioning
confidence: 99%
“…TRPC channel activation is downstream of phospholipase C (PLC), so G protein-coupled receptor signaling events that activate PLC are poised to open VGCCs. Of note, the parathyroid hormone that stimulates Ca 2+ influx through VGCCs in ROS 17/2.8 activates PLC (90), and ROS 17/2.8 cells have TPRC3 transcripts (91).…”
Section: Potential Mechanisms Of Voltage-gated Ca 2+ Channel Regulati...mentioning
confidence: 99%
“…PTH is synthesized by the parathyroid glands and acts on kidney and bone to regulate calcium homeostasis [3][4][5]. PTH stimulates multiple intracellular signals that include cyclic adenosine monophosphate (cAMP) [6][7][8][9], inositol phosphate, and calcium [10][11][12][13][14][15], and activates both protein kinase A [16] and C [17]. PTHrP, in contrast, is synthesized in multiple tissues with specific spatial and temporal profiles and has largely paracrine functions [4,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…PTHRP has also been shown to inhibit collagen synthesis in avian epiphyseal cartilage cells (Pines et al 1990). These effects of PTHRP may be mediated through its activation of protein kinase C and inositol trisphosphate second messenger systems that were observed in UMR-106 and ROS 17/28 osteoblast-like osteosarcoma cells (Babich et al 1990;Cosman et al 1989).…”
Section: Actions Of Pthrp On Bone and Kidneymentioning
confidence: 98%
“…Although its overall structure is similar to that of other of Early studies on the structure-function of the ligand have shown that deletion of the two N-terminal amino acids of PTH or PTHRP results in dramatic loss of adenylyl cyclase-stimulating ability (Rabbani et al 1988). without adversely affecting activation of phospholipase C and phosphoinositide synthesis (Cosman et al 1989). More recently, the C-terminal truncated PTH (1-31) has been shown to activate adenylyl cyclase.…”
Section: Note To Usersmentioning
confidence: 99%